A static model for voting on social security - Henning Bohn (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper examines a static voting model for public pensions. The key premise is that families can internalize the cost and benefits of pay-as-you-go programs. A family realizes a net gain if its members collectively receive more in benefits in the current period than they pay in payroll taxes. Abstracting from differences in income, net benefits are positive if the family's retiree-worker ratio exceeds the national average. If a sufficient fraction of retirees have a suitable number of working-age relativesnot too few and not too manythen a majority of voters belongs to families with above average retiree-worker ratios.
Keywords: H55; 330; social security; public pensions; voting model; Gesetzliche Rentenversicherung; Rentenfinanzierung; Lohnsteuer; Familienökonomik; Public Choice; Theorie